PENGARUH BYSTANDER TERHADAP BODY SHAMING DI INSTAGRAM OLEH MAHASISWA - Vika Aditya Novitasari, - (2022)
Instagram has developed into a social media that is favored by Indonesian netizens. However, it was also found that there were many acts of cyber bullying in the form of negative comments that led to body shaming in Instagram. These negative comments can be found easily by Instagram users, these comments are not only known by victims and perpetrators of cyber bullying, but other parties as witnesses (bystanders). Because bystanders make up the largest number of social media users, it's vital to understand their role in an issue that's growing on Instagram, particularly when it comes to body shaming. This study aims to find out about the influence of bystanders represented by students on Instagram social media in dealing with body shaming actions through the comments sections. This study uses a quantitative approach with inferential statistical methods, the results showed that: (1) students as bystanders have good prosocial knowledge but do not carry out prosocial behavior to help victims of cyber bullying on Instagram, the tendency of bystanders is the outsider category, (2) students find the existence of body shaming actions through the Instagram comment sections which is based on ideal physical beauty standards, (3) the effect of bystander on body shaming has a value that is not significant, so the effect is small.